Managerial Preference, Asymmetric Information, and Financial Structure - BLAZENKO, GEORGE W. (Journal of Finance, 1987)
ABSTRACT If firm performance affects managers' wealth or reputation, preferences of managers dominate firms' financing decisions. When information about real asset investment is symmetric, managers finance exclusively with equity. If managers know more about asset quality than do investors and if managers are sufficiently risk averse, they signal high‐quality projects with debt. Increases in collateral value decrease risky debt use. Increases in interest rates that do not change productive opportunities increase debt use. The explanation for these and further results is based on underpricing of equity and overpricing of debt at the margin.